Heat Accumulation Mechanism of the Gaoyang Carbonatite Geothermal Field, Hebei Province, North China - Zhang, Baojian; Wang, Siqi; Kang, Fengxin; Wu, Yanqiu; Li, Yanyan; Gao, Jun; Yuan, Wenzhen; Xing, Yifei (Frontiers in Earth Science, 2022)
The paper reports the latest exploration achievements of deep buried hill geothermal resources in the geothermal field. Combined with these results, the heat control factors and heat accumulation mechanism of the deep carbonatite geothermal field are confirmed. The westward subduction of the Pacific plate caused obvious damage to the eastern North China Craton, and greatly reduced the thickness of the lithosphere and crust. This process facilitates the conduction of mantle-derived heat to shallow crust. Deep strike-slip faults (e.g., Maxi fault) cut through the lithosphere, leading the deep mantle-derived heat and magma migrate into the crust. The heat accumulates from the depression with low thermal conductivity to the uplift with high thermal conductivity. Groundwater is heated up by deep cycle and convection along faults. The catchment of regional karst groundwater also has a certain effect on the heat accumulation. The Gaoyang geothermal field was formed by these factors.